1997
DOI: 10.1094/cchem.1997.74.5.548
|View full text |Cite
|
Sign up to set email alerts
|

Study of Three‐Dimensional Structure of Wheat Starch Granules Stained with Remazolbrilliant Blue Dye and Extracted with Aqueous Sodium Dodecyl Sulfate and Mercaptoethanol Solution

Abstract: Wheat starch granules were obtained from soft wheat flour by acetic acid fractionation (pH 3.5), and the starch was stained by reaction with Remazolbrilliant blue (RBB) dye. RBB‐stained starch was extracted with 1% sodium dodecyl sulfate (SDS) and 1% 2‐mercaptoethanol (ME) for 14.5 hr at room temperature. This extraction step was repeated five times (extracts 1–5). SDS‐ME extracts were subjected to size‐exclusion column chromatography, and comparisons of their profiles for specific absorbance at 650 nm (A650) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…According to Seguchi (1995), aqueous SDS solutions cause granule destabilisation at both room temperature and 50°C, and thus allow granule gelatinisation at lower temperatures. Granule swelling is required to remove the internal higher molecular weight proteins (59 Â 10 3 -149 Â 10 3 ) in 1-2% SDS solution at or above 50°C (Skerritt, Frend, Robson, & Greenwell, 1990).…”
Section: Protein Content Analysismentioning
confidence: 99%
“…According to Seguchi (1995), aqueous SDS solutions cause granule destabilisation at both room temperature and 50°C, and thus allow granule gelatinisation at lower temperatures. Granule swelling is required to remove the internal higher molecular weight proteins (59 Â 10 3 -149 Â 10 3 ) in 1-2% SDS solution at or above 50°C (Skerritt, Frend, Robson, & Greenwell, 1990).…”
Section: Protein Content Analysismentioning
confidence: 99%
“…These authors, in the course of one of the most extensive investigations of internal starch granule-associated proteins to date, investigated the effects on the yield of SGAPs extracted by a buffer solution (50 mM Tris-HCl pH 8.0) containing either 1% or 10% sodium dodecyl sulphate (SDS). The reason for the unexpected high yield of SGAPs with high concentrations of SDS remains to be conclusively explained, however, following the studies of Gough et al [29] and more recently Seguchi [55] regarding the effects of SDS on starch granules it would appear that aqueous SDS solutions cause granule destabilisation (indicated by a loss of birefringence) at both room temperature (RT) and 50°C, and thus allow granule gelatinisation at lower temperatures than normal. Rahman et al comment that the increased yield of SGAP extraction by solutions containing high concentrations of SDS was unexpected and is believed to result from the "unusual properties" of SGAPs.…”
Section: Sgap Quantification: the Influence Of Sds Concentrationmentioning
confidence: 99%
“…"Surface" proteins between 5 and 30 kDa on "A-grade" cereal starch granules can be removed by agitation at RT with either aqueous salt solutions such as 0.1 M NaCl [9,17], 0.05 M NaCl containing 50% (v/v) propan-2-ol [57], a 1 or 2% solution of SDS (optionally with 1% β-2-mercaptoethanol (2-ME) [5,12,13,29,41,55,58], or 10 mM dithiothreitol (DTT) [5]), SDS-PAGE sample buffer solutions [59], 50% (v/v) propan-2-ol [57] or with toluene [8]. It is now known, however, that these extraction methods are unlikely to fully extract "surface" SGAP; Schofield and Greenwell [12] reported that dilute NaCl extracts only 10% of the total SGAP (substantially more than 10% of SGAP is "surface" protein -see Section 3.4 below); Rahman et al [30] have demonstrated that 1 or 2% solutions of SDS do not give maximum yields of SGAPs, and that 10% SDS solutions are probably preferable (although this remains to be verified with "surface" proteins).…”
Section: Extraction Of Starch Granule-associated Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayashi et al [5] showed that the amylose molecules were mainly present in the central portion of the ghost, as indicated by the data of determination of amylose content and column chromatography profiles, and that the ghost central portion is more rigid in the concentrated KI/I 2 solution than the surrounding portion. Seguchi and Kanenaga [6] opened normal wheat starch granules from the equatorial groove by Remazol brilliant blue staining and washing with 1% sodium dodecyl sulfate solution containing 1% 2-mercaptoethanol at room temperature, and showed the presence of double structures. The double structures of the barley starch granule were also reported by Vasanthan et al [7].…”
Section: Introductionmentioning
confidence: 99%